EFFECT OF NEEM (Azadirachta indica) LEAF POWDER ON EGG COMPOSITION PARAMETERS OF COMMERCIAL LAYERS* (Indian Journal of Animal Production and Management, 2014)
A study was conducted on 120 commercial layers (BV3OO) of twenty two weeks old to investigate effect of neem leaf powder (NLP) supplementation on egg composition traits. The experimental birds were randomly divided into four treatment groups viz. groups T1 (control), T2 (0.1% NLP), T3 (0.2 % NLP) and T4 (0.3% NLP). The above mentioned percentages of NLP were supplemented in daily feed up to 8 weeks period. At the end of phase I (22-25 weeks), phase II (26-29 weeks) and overall period (30-33 weeks) the egg composition parameter was analyzed. Egg composition traits (crude protein, crude fat and ash) during phase I, phase II and overall period were found unaffected by supplementation of neem leaf powder. The present study conclusively indicated that neem leaf powder supplementation through feed can be unaffected egg composition parameters in commercial layers.
Keywords: Commercial layers; Neem leaf powder (Azadirachta Indica); Egg composition